Prognostic effect of sarcomatoid dedifferentiation in patients with surgically treated renal cell carcinoma: a matched-pair analysis - Brookman‐May, Sabine D.; May, Matthias; Shariat, Shahrokh F.; Zigeuner, Richard; Chromecki, Thomas; Cindolo, Luca; Schips, Luigi; De Cobelli, Ottavio; Rocco, Bernardo; De Nunzio, Cosimo; Tubaro, Andrea; Feciche, Bogdan; et al. (Clinical genitourinary cancer, 2013)
Background - The aim of this study was to assess the prognostic relevance of SD in patients with RCC. - Patients and Methods - Among 8126 RCC patients surgically treated at 12 academic centers (members of the Collaborative Research on Renal Neoplasms Association [CORONA] project), 316 patients (3.9%) had SD with sarcomatoid areas comprising at least 10% of the tumor tissue. After propensity score-based matched-pair analysis, 281 with and 281 matched RCC patients without SD remained available for direct comparison of cancer-specific survival (CSS). Median follow-up was 36.5 months (interquartile range, 15-82). Uni- and multivariable Cox proportional hazards regression analyses were performed to assess the prognostic value of parameters. - Results - In univariable analysis, there was no difference in CSS between patients with or without SD (1 and 5 years CSS, 79% vs. 83% and 59% vs. 64%, respectively; hazard ratio, 1.21; P = .16). Multivariable analysis in patients with SD identified metastatic dissemination at the time of surgery, pT-stage, nodal status, and tumor size as independent predictors of CSS. This study was limited by its retrospective multicenter design and lack of central histopathological review. - Conclusion - Sarcomatoid dedifferentiation was not an independent predictor of CSS in surgically treated RCC patients in the present matched-pair series. Because pathology reports form the basis on which study specimens are selected for further studies, which are clearly needed to advance our understanding of the prognostic value of SD in RCC, it is imperative that pathologists reliably report on absence or presence and the estimated percentage of a coexisting sarcomatoid component.